Constitutional and legal framework of gender justice in Germany - Marita Körner (Fachhochschule für Wirtschaft Berlin, IMB Institute of Management Berlin, 2006)
It has been a long journey to get from the 1950s when the natural difference between men and women was accepted as a reasonable ground for legal and social inequality to today's laws and jurisprudence that aim at compensating for structural disadvantages of women, especially in the workforce. The article lines out this journey, showing that the legal framework for gender justice rests on three pillars: firstly Art. 3 of the Constitution with its different phases of a more and more farreaching interpretation, secondly equal treatment provisions in European Community Law, which have massively influenced the development of the third pillar, German statute law with a growing number of gender justice oriented labour law provisions on the one hand and Equal Treatment Acts for the public service on the other hand. The subject of gender justice is more than ever on the agenda of the legislator as several EC-directives on the matter have to be implemented in German law. The draft of an Anti-Discrimination Act is likely to be enacted in the second half of 2006.
Keywords: 340